2021
DOI: 10.1093/ehjdh/ztab010
|View full text |Cite
|
Sign up to set email alerts
|

Mobile application to optimize care for ST-segment elevation myocardial infarction patients in a large healthcare system, STEMIcathAID: rationale and design

Abstract: Technological advancements have transformed healthcare. System delays in transferring patients with ST- segment elevation myocardial infarction (STEMI) to a primary percutaneous coronary intervention (PCI) center are associated with worse clinical outcomes. Our aim was to design and develop a secure mobile application, STEMIcathAID, streamlining communication and coordination between the STEMI care teams to reduce ischemia time and improve patient outcomes. The app was designed for transfer of patients with ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…19) Moreover, it becomes important to establish a comprehensive STEMI care system, incorporating an ECG transmission system to swiftly and accurately diagnose patients with STEMI. 20) The present study demonstrated an independent association between pretransfer aspirin administration and achievement of initial TIMI-3 flow in the IRA, indicating that pretransfer aspirin administration may partially contribute to the beneficial effects of PCI on infarct size in patients with STEMI. Platelet activity can be inhibited within an hour of aspirin administration, which typically reaches peak plasma concentration within 30-40 minutes.…”
Section: Discussionsupporting
confidence: 58%
“…19) Moreover, it becomes important to establish a comprehensive STEMI care system, incorporating an ECG transmission system to swiftly and accurately diagnose patients with STEMI. 20) The present study demonstrated an independent association between pretransfer aspirin administration and achievement of initial TIMI-3 flow in the IRA, indicating that pretransfer aspirin administration may partially contribute to the beneficial effects of PCI on infarct size in patients with STEMI. Platelet activity can be inhibited within an hour of aspirin administration, which typically reaches peak plasma concentration within 30-40 minutes.…”
Section: Discussionsupporting
confidence: 58%
“…Although, this application does not provide information of patient position or communication channels between members of the team, an special mention has to be done for being the first one to be proposed to support STEMI management. The second application is STEMIcathAID, proposed by Krishnamoorthy et al [11]. This mobile app optimizes care for STEMI patients and facilitates electronic extraction of relevant performance metrics to improve allocation of resources and reduction of costs.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al [9] evaluated how the use of a smartphone social network system in a regional STEMI network can reduce the ischemic time. Focused on STEMI management, Dickson et al [10] proposed STOP-STEMI an application to improve the coordination of STEMI care and Krishnamoorth [11] proposed an HIPAA compliant app for the transfer of patients with STEMI.…”
Section: Introductionmentioning
confidence: 99%